Needs analysis for developing a laboratory manual of Cryptogamic botany to build scientific character on student biology education - Aulia Ajizah; Nahadi Nahadi; Chairil Faif Pasani; Encep Syarief Nurdin (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2024)
The Cryptogamic botany course is supported by practical activities. The laboratory activities involve the observation of the morphology and taxonomy of lower plants. Observational activities focusing on lower plants require precision, creativity, curiosity, and objectivity from each participant. However, the available practical guide does not explicitly address these scientific characteristics. The objective of this research is to gather preliminary information and analyze the need for the development of a Cryptogamic botany practical guide aimed at fostering scientific character among students. This study is descriptive in nature, with data collection conducted through questionnaires and interviews involving 73 students and 4 lecturers responsible for the Lower Plants (Cryptogamic botany) course as respondents. The data were analyzed descriptively based on the percentage of respondent answers for each aspect in question. The results showed that 84.3% of the students strongly agreed, and 15.7% agreed, on the need for a practical guide integrated with scientific character. Furthermore, 58.8% of students preferred that this integration be explicitly presented in the practical guide, while others preferred it to be incorporated in the form of questions. All lecturers agreed on the integration of scientific character in the practical guide, with 25% favoring explicit inclusion, 25% supporting its incorporation through questions, and 50% advocating for it to be framed within a learning model. The development of a Cryptogamic botany practical guide integrating scientific character is deemed essential.Abstrak. Mata kuliah Cryptogamic botany ditunjang oleh kegiatan praktikum. Kegiatan pengamatan dengan objek tumbuhan rendah menuntut ketelitian, kreatifitas, rasa ingin tahu dan objektifitas terhadap data dari setiap praktikan. Panduan praktikum yang tersedia belum memuat secara eksplisit karakter ilmiah yang dimaksud. Tujuan penelitian adalah untuk mengumpulkan informasi awal dan untuk menganalisis kebutuhan untuk pengembangan panduan praktikum Cryptogamic botany dalam rangka membangun karakter ilmiah para praktikan. Penelitian ini merupakan penelitian deskriptif. Pengumpulan data menggunakan instrumen berupa kuesioner dan wawancara yang melibatkan 73 mahasiswa dan 4 orang dosen pengampu mata kuliah Tumbuhan Rendah (Cryptogamic botany) sebagai responden. Data dianalisis secara deskriptif berdasarkan penghitungan persentase jawaban responden pada setiap aspek yang dipertanyakan. Hasil penelitian menunjukkan bahwa kebutuhan mahasiswa terhadap panduan praktikum yang terintegrasi karakter ilmiah dengan persentase 84,3% sangat setuju dan 15,7% menyatakan setuju. Sebanyak 58,8% mahasiswa menghendaki pengintegrasiannya dipaparkan secara jelas di dalam panduan praktikum, dan yang lainnya menghendaki dituangkan dalam bentuk pertanyaan. Seluruh dosen pengampu mata kuliah menyatakan setuju untuk pengintegrasian karakter ilmiah dalam panduan praktikum secara jelas (25%), 25% menghendaki dituangkan dalam bentuk pertanyaan. dan dikemas dalam suatu model pembelajaran (50%). Panduan praktikum Cryptogamic botany yang mengintegrasikan karakter ilmiah menjadi hal yang penting.